DINAMIKA IMPLEMENTASI KEBIJAKAN LAYANAN EAZY PASSPORT PADA KANTOR IMIGRASI TANJUNG PERAK - Caesar Demas Edwinarta (FISIP UWP, 2022)
This research is a study of the implementation of the Eazy Passport service policy at the Tanjung Perak Immigration Office. The Eazy Passport service is an innovation initiated by the Directorate General of Immigration to overcome the problem of declining number of passport applications caused by the Covid-19 pandemic. This study uses a qualitative approach with a case study method that examines the implementation of the Eazy Passport service policy and the dinamics that occur in the development. The result of the analysis carried out describe the dynamics of the implementation of the Eazy Passport service from the beginning of the implementation to the renewal that occur covering aspects of the procedures and terms of service, as well as efforts to make it a regular agenda at each certain period. This study of the dinamics of policy implementation, which has been implemented for more than a year, is expected to be able to provide an overview of policy implementation in the Immigration Office as well as become a material for evaluation and reformulation to be able to create better policy implementation in the future.